Synthesis and Crystal Structure of 2-(Dichloromethyl)-2-(4-nitrophenyl)-1,3-dioxane - Fei Ye; Chang-Ying Sun; Ying Fu (Journal of Chemistry)
A new compound, 2-dichloromethyl-2-p-nitrophenyl-1,3-dioxane, was synthesized and characterized. The crystal structure of the title compound (C11H11Cl2NO4, Mr=292.11) has been determined by single-crystal X-ray diffraction. The crystal is of monoclinic, space group P21/c with a=11.013(2) Å, b=14.653(3) Å, c=7.8693(16) Å, α=90°, β=97.06(3)°, γ=90°, V=1260.3(4) Å3, Z=4, F(000)=600, Dc=1.540 mg/cm3, the final R1=0.0508, and ωR2=0.1072 for observed reflections with I>2σI. A total of 12162 reflections were collected, of which 2867 were unique (Rint=0.06999).